THE EFFECT OF PYROLYSIS DURATION ON THERMAL CONDUCTIVITY, STABILITY, AND VISCOSITY OF DISPERSED PCB-BASED PARTICLES IN THERMAL FLUID - Putra, Wahyuaji Narottama; Ariati, Myrna; Suharno, Bambang; Ferdian, Deni; Ulum, Reza Miftahul (Jurnal Rekayasa Mesin, 2023)
Solid particles have a higher thermal conductivity compared to a fluid. Therefore, it is a common practice to disperse solid particles inside a base fluid to increase its thermal conductivity. The particle-dispersed fluid is called a thermal fluid. Thermal fluid, such as a coolant, is widely used as a heat transfer fluid. Several types of particles can be used to increase the thermal conductivity of the fluid, i.e., metallic particles, metal-oxide particles, or even carbon-based particles. In this research, a carbon-based particle was used as the dispersed particle. The particle was obtained by processing electronic waste, specifically Printed Circuit Board (PCB). The PCB was pyrolyzed for variable duration at 15, 30, and 45 minutes to increase the carbon content. After pyrolyzing, the particle was milled to reduce its size. Subsequently, the PCB particle was added to distilled water. Sodium Dodecylbenzene Sulfonate (SDBS) was added as a surfactant to increase fluid stability and prevent particle agglomeration. Thermal conductivity was improved by up to a 13% increase at the 15-minute pyrolysis. Adding SDBS surfactant also improves the thermal fluid's stability to -29,1 mV. The fluid's viscosity was slightly increased up to a maximum of 0.984 mPa.S.